The potential of mangroves as blue carbon in the perspective of maritime law in Indonesia - Nathania Permata Satriawan; Hera Alvina Satriawan (Priviet Social Sciences Journal, 2026)
Climate change has increased the urgency of coastal ecosystem management as a part of global carbon emission mitigation strategies. Mangrove forests are one of the most significant coastal ecosystems because of their capacity to absorb and store large amounts of blue carbon. This study aims to analyze the potential of mangroves as blue carbon from the perspective of maritime law in Indonesia and to examine the strengthening of legal regulations through Government Regulation or Peraturan Pemerintah (PP) No. 27 of 2025 concerning the Protection and Management of Mangrove Ecosystems. This study utilizes a normative legal research methodology based on statutory and conceptual frameworks. Legal materials were obtained from legislation, scientific journals, and relevant literature on mangrove protection and climate change policies. The results indicate that mangroves serve important functions as coastal ecosystem protectors, natural carbon sinks, and climate change mitigation instruments in the framework of sustainable development. The enactment of PP No. 27 of 2025 strengthens the legal basis for mangrove management through integrated measures involving the protection, rehabilitation, conservation, and damage control of mangrove ecosystems. Nevertheless, the implementation of such regulations still encounters challenges, including weak supervision, overlapping institutional authority, and increasing pressure from coastal development activities. Therefore, policy synergy and strengthened governance are required to ensure the sustainability of Indonesia’s mangrove ecosystems.